Sleep deprivation enhances inter-stimulus interval effect on vigilant attention performance. Issue 12 (28th September 2018) - Yang, Fan Nils; Xu, Sihua; Chai, Ya; Basner, Mathias; Dinges, David F; Rao, Hengyi
Abstract: Study Objective: Sleep deprivation significantly reduces the ability to maintain a consistent alertness level and impairs vigilant attention. Previous studies have shown that longer inter-stimulus interval (ISI) are associated with faster reaction times (RTs) on the Psychomotor Vigilance Test (PVT). However, whether and how sleep deprivation interacts with this ISI effect remains unclear. Methods: N = 70 healthy adults (age range 20–50 years, 41 males) participated in a 5-day and 4-night in-laboratory controlled sleep deprivation study, including N = 54 in the experimental group with one night of total sleep deprivation and N = 16 in the control group without sleep loss. All participants completed a neurobehavioral test battery every 2 hours while awake, including a 10-minute standard PVT (PVT-S, N = 1626) and a 3-minute brief PVT (PVT-B, N = 1622). The linear approach to threshold with ergodic rate (LATER) model was used to fit the RT data. Results: RT decreased significantly with longer ISI on the PVT-S and PVT-B. Increased ISI effect was found for both PVT-S and PVT-B during sleep deprivation compared to baseline or recovery sleep in the experimental group, whereas no differences in the ISI effect were found in the control group. The LATER model fitting indicated that changes in perceptual sensitivity rather than threshold adjustment may underlie the ISI effect. Conclusions: Both standard and brief PVT showed a similar ISI effect on vigilant attention performance. Sleep deprivation increased the ISI effect on both PVT-S and PVT-B, which may be due to impaired temporal resolution and time estimation after sleep loss.